Romancing the Past: History, Love, and Genre in Vincent Ward’s River Queen - Roger Nicholson (Journal of Popular Romance Studies, 2011)
Theorists tend to conceive the role of narrative in historiography as emplotment (Hayden White), giving “direction” to readers’ thoughts by its generic choices. This paper argues that in such contexts genre is often hybrid, coupled with other genres or even divided internally. A case in point is the New Zealand film River Queen (Vincent Ward, 2005), where romance complicates and extends an historical narrative of violent, colonial hostilities. Romance glamorizes history; it is also a complex form in itself: love romance, quest, captivity narrative. History becomes affective and intimate. At some level, here, love offers history the fantasy of a “new community” (Regis); or, perhaps just a measure of “restitution” (Sebald).